Dynamic performance evaluation with deadlines: The role of commitment - Chia-Hui Chen; Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2017)
We consider an environment in which a principal hires an agent and evaluates his productivity over time in an ongoing relationship. The problem is embedded in a continuoustime model with both hidden action and hidden information, where the principal must induce the agent to exert effort to facilitate her learning process. The value of committing to a deadline is examined in this environment, and factors which make the deadline more profitable are identified. Our framework generates a unique recursive equilibrium structure under no commitment which can be exploited to obtain a full characterization of equilibrium. The analysis allows us to evaluate the exact value of commitment for any given set of parameters and provides insight into when it is beneficial to commit to an evaluation deadline at the outset of a relationship.
Keywords: D82; D83; 330; dynamic agency; deadlines; experimentation; commitment; up-or-out contracts